Establishment of Chimerism and Organ Transplant Tolerance in Laboratory Animals: Safety and Efficacy of Adaptation to Humans - Lowsky, Robert; Strober, Samuel (Frontiers in Immunology, 2022)
The definition of immune tolerance to allogeneic tissue and organ transplants in laboratory animals and humans continues to be the acceptance of the donor graft, rejection of third party grafts, and specific unresponsiveness of recipient immune cells to the donor alloantigens in the absence of immunosuppressive treatments. Actively acquired tolerance was achieved in mice more than 60 years ago by the establishment of mixed chimerism in neonatal mice. Once established, mixed chimerism was self-perpetuating and allowed for acceptance of tissue transplants in adults. Successful establishment of tolerance in humans has now been reported in several clinical trials based on the development of chimerism after combined transplantation of hematopoietic cells and an organ from the same donor. This review examines the mechanisms of organ graft acceptance after establishment of mixed chimerism (allo-tolerance) or complete chimerism (self-tolerance), and compares the development of graft versus host disease (GVHD) and graft versus tumor (GVT) activity to complete and mixed chimerism. GVHD ,GVT activity , and complete chimerism are also discussed in the context of bone marrow transplantation to treat hematologic malignancies. The roles of transient versus persistent mixed chimerism in the induction and maintenance of tolerance and organ graft acceptance in animal models and clinical studies are compared. Key differences in the stability of mixed chimeras and tolerance induction in MHC matched and mismatched rodents, large laboratory animals, and humans are examined to provide insights into the safety and efficacy of translation of results of animal models to clinical trials.